Oral and Cranial Implants Recent Research Developments - Devlin, Hugh.; Nishimura, Ichiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Dentists are routinely faced with a huge choice of implant systems from different manufacturers, each of whom claims that its own particular system has advantages over the others. There is consequently a need for an evidence-based review of the field that offers authoritative practical guidance for dental practitioners. Oral and Cranial Implants: Recent Research Developments has been written with this in mind. It brings together all the recent key developments in implant research and discusses the underlying science relating to implant procedures and failures. Relevant literature is reviewed and clear practical advice is offered. This book will be ideal for dentists wishing to obtain a snapshot of research in the field and will also be useful for specialists in restorative dentistry. The authors are recognized leading authorities who are well equipped to evaluate the applications and challenges associated with implants.
Peri-implant Diseases: Peri-implant Mucositis and Peri-implantitis -- Cranial Implants -- The Bisphosphonate-treated Patient -- The Genetic Background of Implant Failure -- The Biomechanical Aspects of Implants and why they fail.
Keywords: Dentistry; Surgery; Biomaterials; Dentistry; Dentistry; Oral and Maxillofacial Surgery; Biomaterials